FIP1L1–PDGFRA positive chronic eosinophilic leukaemia and associated central nervous system involvement. Issue 5 (6th February 2008) - Williams, C; Kalra, S; Nath, U; Bown, N; Wilson, V; Wilkins, B S; Neylon, A J
Abstract : Interstitial deletion involving chromosome 4q12 generates the novel tyrosine kinase fusion protein encoded by FIP1L1–PDGFRA, which is present in many patients previously labelled as having hypereosinophilic syndrome, initially reported in 2003. Reports in recent literature document excellent clinical and molecular response to the tyrosine kinase inhibitor imatinib (Glivec). This report describes the case of a 58-year-old lady, diagnosed with FIP1L1–PDGFRA positive hypereosinophilic disorder, who subsequently developed symptoms related to an intracranial lesion. Biopsy and molecular genetic studies confirmed a diffuse infiltrative lesion, with evidence of FIP1L1–PDGFRA gene fusion. Initiation of imatinib treatment led to impressive clinical and radiological response.